Combination Administration of Stichopus hermaniiGel and Hyperbaric Oxygen Therapy the number of fibroblasts in diabetes mellitus rats with periodontitis - Faraziza Maulana; Dian Mulawarmanti; Fanny M.Laihad (Denta Journal Kedokteran Gigi, 2017)
Background: Periodontitis is the most severe complication in oral cavity to diabetes mellitus. Stichopus hermanii contain GAG, a polysaccharide which very useful in wound healing. Hyperbaric oxygen therapy is effective repairing ischemia, hypoxia, and is used as adjuvant therapy. Purpose: To determine effect of administration of Stichopus hermanii (SH) 3% gel and hyperbaric oxygen therapy 3x30 minutes with 5 minute intervals in 7 consecutive days to the number of fibroblasts in ligament periodontal diabetes mellitus rats with periodontitis. Materials and Methods: The experiment design is factorial design. Rats are inducted with STZ single dose 65 mg/kgBB to make them suffer DM and are inducted with P.gingivalis 1x109sel/ml for 5 days straight to make them suffer periodontitis. 20 male wistar rats are divided into 5 groups. K- (control), K1 (STZ+P.Gingivalis), K2(STZ+P.Gingivalis+SH), K3(STZ+P.Gingivalis+HBO), K4(STZ+P.Gingivalis+SH+HBO). After 52 days treatment, rats is terminated to make a HPA Sample from the mandible and fibroblast is counted with 400x magnification. Result: One-way Annova here were significant differences (p<0,05) in K- (32.300 ± 11.381), K1 (31.725 ± 5.590), K2 (54.225 ± 7.165), K3 (49.725 ± 10.088), K4 (72.075 ± 9.342). Conclusion: administration of Stichopus hermanii 3% gel combination and 2.4 ATA hyperbaric oxygen 3x30 minutes a day with 5 minutes intervals in 7 consecutive days can increase the number of fibroblasts in diabetes mellitus rats with periodontitis.